Covalent Organic Frameworks with Chirality Enriched by Biomolecules for Efficient Chiral Separation - Zhang, Sainan; Zheng, Yunlong; An, Hongde; Aguila, Briana; Yang, Cheng‐Xiong; Dong, Yueyue; Xie, Wei; Cheng, Peng; Zhang, Zhenjie; Chen, Yao; Ma, Shengqian (Angewandte Chemie International Edition, 2018)
The separation of racemic compounds is important in many fields, such as pharmacology and biology. Taking advantage of the intrinsically strong chiral environment and specific interactions featured by biomolecules, here we contribute a general strategy is developed to enrich chirality into covalent organic frameworks (COFs) by covalently immobilizing a series of biomolecules (amino acids, peptides, enzymes) into achiral COFs. Inheriting the strong chirality and specific interactions from the immobilized biomolecules, the afforded biomolecules⊂COFs serve as versatile and highly efficient chiral stationary phases towards various racemates in both normal and reverse phase of high‐performance liquid chromatography (HPLC). The different interactions between enzyme secondary structure and racemates were revealed by surface‐enhanced Raman scattering studies, accounting for the observed chiral separation capacity of enzymes⊂COFs. COF chirality: A general and efficient strategy has been developed to introduce chirality into covalent organic frameworks (COFs) by covalently immobilizing biomolecules into achiral COFs. The biomolecules⊂COFs can serve as chiral stationary phases for efficient chiral separation of a broad range of racemates.